Temperature Dependence of Dielectric Constant on Pure Polymethyl Methacrylate - Mittal, Alok; Jain, Vineeta; Mittal, Jyoti (Asian Journal of Chemistry, 2010)
Temperature variation is investigated for the dielectric constant of polar polymer, pure polymethyl methacrylate (PMMA). Measurements were carried out in the temperature range 35-80°C at various applied a.c. frequencies. The obtained results indicate that the dielectric constant and dielectric loss increases with increase in temperature due to enhancement of the polarization.